GAMBARAN FAKTOR IBU YANG TERKAIT DETEKSI DINI KEHAMILAN BERISIKO DI KABUPATEN BREBES - Praba Ginandjar; Lintang Dian Saraswati (Kesmas Indonesia, 2012)
ABSTRACT High risk pregnancy could be early detected and handled if pregnant mothers routinely visit healthcare service, thus reduce maternal death. Internal factors of pregnant mothers related to the compliance of pregnancy examination are age, education, work, income and knowledge on high risk pregnancy. The study intended to describe factors related to early detection of high risk pregnancy in District of Brebes. This was a descriptive study with rapid survey method. Study subjects should meet the criteria of having labor 0-4 months baby (both live of death) at the time the study conducted and living in selected cluster. There were 30 clusters, and 7 subjects were selected from each of it, therefore the total subject was 210 mothers. The result showed mothers had low level of education, most of them were housewives, with equal number of low and high income. Age ranged from 16 to 43 years, it meant there were still pregnant mothers out of optiimal reproductive age. Anemia was the highest risk of pregnancy in District of Brebes and there was still hypertension case in pregnant mothers. Knowledge of high risk pregnancy was low, with most of information source from books. It was suggested to health officer to increase their role in giving information on high risk pregnancy to pregnant mothers in District of Brebes. Keywords: high risk pregnancy, knowledge, anemia, hypertension Kesmasindo Volume 5(1) Januari 2012, hlm. 44-51